A comparison of earnings measures from longitudinal and cross-sectional surveys: evidence from the UK - Marco Francesconi; Holly Sutherland; Francesca Zantomio (University of Essex, Institute for Social and Economic Research (ISER), 2009)
This paper compares earnings data from the BHPS with those collected in the FRS, contrasting two different points in time (1995/96 and 2003/04), allowing us to assess the possible extent of differential attrition in the BHPS data. We perform non-parametric tests of equality at the centre of the distributions and over the whole earnings distributions. We then apply multivariate regression methods to establish whether the earnings data yield different results in relation to three typical uses of earnings data. The two surveys have fairly similar earnings data in the first comparison year, while sizable differences emerge in the later comparison. This finding suggests the important role played by attrition and vintage effects.
Keywords: 330